Pengaruh Corporate Social Responsibility terhadap Corporate Image pada Perusahaan Rokok di Indonesia - Sigit Pramono; Rini Safitri; Dunga Dwi Barinta (Akademi Akuntansi YKPN Yogyakarta, 2020)
This study aims to measure the effect of CSR on Corporate Image. The research approach used explanatory research analysis. The sample of this research is people who know about CSR which is applied in cigarette companies. The implementation of CSR for cigarette companies is important as a form of contribution to society. However, the implementation of CSR in cigarette companies is still considered as part of a promotional strategy alone. The debate on the application of CSR to the cigarette industry is an interesting part to discuss. The results of this study reveal that CSR is a determining factor in shaping and strengthening a company's image. In addition, the findings in this study confirm that Altruistic Responsibility which focuses on improving the welfare of the community will have a big impact on the company, the role of Altruistic Responsibility as a component of CSR that shapes the company's image will have an impact on company profitability, logistical support, and strengthen public trust.